TIGA LEMPENG PRASASTI LANGKAN DARI RAJA JAYASAKTI - Nirmala Sari, Ni Made (Humanis, 2016)
Inscription is one of the archaeological remains in the form of writing, the inscription is Prasasti Langkan of the king Jayasakti. The inscription found in Banjar Langkan, Pengotan Village, Bangli District of Bangli Regency and the  inscription saved the Puseh temple in Banjar Langkan, and maintained by local. This study aims to find out more in depth how the linguistic and socio-political, economic, and cultural contained in the inscription. Data collection techniques use in this study is the observation, interviews and literature. Data analysis technicques such as qualitative analysis and comparative analysis use in this study helps reveal problem. In the inscription Langkan explainedthat the people there werenine heads of families because in just go to another  village. Inscription Langkan also discussed the linguistic and taxation that is tax exemted and which shall be paid by the local to the king. In addition to taxes, other economic activity in the inscription Langkan that is by raising and farming. In addition it also explained about the position in the kingdom as well as religion and believe systems.
Keywords: Inscription Langkan, jayasakti, Epigraphy